Reviews - W. Keith Duffy; Elizabeth Vander Lei; Marian MacCurdy (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
Reviews W. Keith Duffy. Memoirs of Soul: Writing your Spiritual Autobiography. (Nan Phifer, 2002). Elizabeth Vander Lei. A Communion of Friendship: Literacy, Spiritual Practice, and Women in Recovery. (Beth Daniel, 2003). Marian MacCurdy. Writing To Save Your Life. (Michele Weldon, 2001).